Stress‐dependent transport properties of fractured arkosic sandstone. Issue 3 (5th April 2016) - French, M. E.; Chester, F. M.; Chester, J. S.; Wilson, J. E.
Abstract: We measure the fluid transport properties of microfractures and macrofractures in low‐porosity polyphase sandstone and investigate the controls of in situ stress state on fluid flow conduits in fractured rock. For this study, the permeability and porosity of the Punchbowl Formation sandstone, a hydrothermally altered arkosic sandstone, were measured and mapped in stress space under intact, microfractured, and macrofractured deformation states. In contrast to crystalline and other sedimentary rocks, the distributed intragranular and grain‐boundary microfracturing that precedes macroscopic fracture formation has little effect on the fluid transport properties. The permeability and porosity of microfractured and intact sandstone depend strongly on mean stress and are relatively insensitive to differential stress and proximity to the frictional sliding envelope. Porosity variations occur by elastic pore closure with intergranular sliding and pore collapse caused by microfracturing along weakly cemented grain contacts. The macroscopic fractured samples are best described as a two‐component system consisting (i) a tabular fracture with a 0.5‐mm‐thick gouge zone bounded by 1 mm thick zones of concentrated transgranular and intragranular microfractures and (ii) damaged sandstone. Using bulk porosity and permeability measurements and finite element methods models, we show that the tabular fracture is at least two orders of magnitude more permeable than the host rock at mean stresses up to 90 MPa. Further, we show that the tabular fracture zone dilates as the stress state approaches the friction envelope resulting in up to a three order of magnitude increase in fracture permeability. These results indicate that the enhanced and stress‐sensitive permeability in fault damage zones and sedimentary basins composed of arkosic sandstones will be controlled by the distribution of macroscopic fractures rather than microfractures.